The village of eight graves - Yokomizo, Seishi 1902-1981 (Pushkin Vertigo, 2021)
Nestled deep in the mist-shrouded mountains, The Village of Eight Graves takes its name from a bloody legend: in the Sixteenth Century eight samurais, who had taken refuge there along with a secret treasure, were murdered by the inhabitants, bringing a terrible curse down upon their village. Centuries later a mysterious young man named Tatsuya arrives in town, bringing a spate of deadly poisonings in his wake. The inimitably scruffy and brilliant Kosuke Kindaichi investigates